(untitled) (Journal of Civil Engineering Researchers, 2024)
This paper presents a comprehensive review of shallow foundations, floor slabs, and deep foundations, focusing on drilled piers, micropiles, aggregate piers, and stone columns. The study aims to consolidate definitions, design methodologies, and construction recommendations pertinent to these foundation types. Shallow foundations, including mat and spread footings, and floor slabs are reviewed with respect to their design considerations and construction techniques, emphasizing their role in efficiently supporting superstructures. Deep foundations such as drilled piers and micropiles are evaluated for their capacity to transfer loads to deeper, more stable layers of soil. The review includes discussions on their design principles, installation methods, and performance in different geotechnical contexts. Additionally, aggregate piers and stone columns are explored as ground improvement techniques, offering insights into their design parameters and construction practices to enhance soil-bearing capacity and mitigate settlement issues. By synthesizing current literature and engineering practices, this review aims to provide engineers, researchers, and practitioners with a comprehensive resource for understanding the complexities of foundation design and construction. Key recommendations are offered to guide future research and practical applications in the field of geotechnical engineering.